Detecting damaged reinforcement bars in concrete structures using guided waves. (2017) - Masri, Evelyne El; Ferguson, Neil; Waters, Timothy
Abstract: Many engineering structures must be inspected or monitored throughout their serviceable life to ensure their safe operation. In the case of reinforced concrete structures, the most common cause of premature failure is corrosion of the steel reinforcement bars that must be pre-empted. Modal based techniques are popular, since they can potentially detect damage using sensors placed remotely from the damage site. However, changes in modal parameters due to damage can be masked by their sensitivity to environmental factors and changes to the boundary conditions that are unrelated to damage. In this respect, wave based techniques provide a potential alternative. In this paper, wave propagation is modelled in a damaged steel reinforced concrete beam. The damaged section is modelled in conventional finite elements and this is coupled to wave finite element models (WFE) of the undamaged sections on either side. This hybrid modelling approach facilitates a wave based analysis of a one dimensional structure with potentially geometrically complex damage. A numerical case study is presented for a locally damaged beam represented by a loss of thickness of one reinforcement bar. It is shown that some wave modes, that feature deformation of the cross section, exhibit a strong reflection close to their cut-on frequency. This is due to the difference in cut-on frequency between the damaged and undamaged sections. A damage detection method is outlined in which the amplitudes of incident and reflected waves of low wave number are compared. No a priori knowledge of the dispersion curves is necessary. In numerical simulations, a reduction in the ratio of the reflected to incident wave amplitudes is seen in the vicinity of cut-on frequencies.